2013
DOI: 10.1007/s11469-013-9460-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy (CBT) and Meditation Awareness Training (MAT) for the Treatment of Co-occurring Schizophrenia and Pathological Gambling: A Case Study

Abstract: There is a paucity of interventional approaches that are sensitive to the complex needs of individuals with co-occurring schizophrenia and pathological gambling. Utilizing a singleparticipant design, this study conducted the first clinical evaluation of a novel and integrated non-pharmacological treatment for a participant with dual-diagnosis schizophrenia and pathological gambling. The participant underwent a 20-week treatment course comprising: (i) an initial phase of second-wave cognitive behavioral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Apart from three case reports (Borras & Huguelet, 2007;Potenza & Chambers, 2001;Shonin, VanGordon, & Griffiths, 2014), there is only one controlled trial that tested the clinical effectiveness of a cognitive-behavioral program specifically adapted for individuals with GD with chronic schizophrenia, with post-treatment and 3, 6, and 12-month follow-up assessments. Adaptation of CBT for these individuals dually diagnosed with GD and chronic schizophrenia took into account several aspects: The active role of the therapist to help patients fulfil the self-reports; the presence of a co-therapist (a family or staff member) in order to enhance motivation for treatment, to encourage patients to carry out in vivo exposure tasks and to check information provided by patients; and the implementation of the program in the stabilization phases of the schizophrenia.…”
Section: Treatment Of Gambling Disorder With Schizophreniamentioning
confidence: 99%
“…Apart from three case reports (Borras & Huguelet, 2007;Potenza & Chambers, 2001;Shonin, VanGordon, & Griffiths, 2014), there is only one controlled trial that tested the clinical effectiveness of a cognitive-behavioral program specifically adapted for individuals with GD with chronic schizophrenia, with post-treatment and 3, 6, and 12-month follow-up assessments. Adaptation of CBT for these individuals dually diagnosed with GD and chronic schizophrenia took into account several aspects: The active role of the therapist to help patients fulfil the self-reports; the presence of a co-therapist (a family or staff member) in order to enhance motivation for treatment, to encourage patients to carry out in vivo exposure tasks and to check information provided by patients; and the implementation of the program in the stabilization phases of the schizophrenia.…”
Section: Treatment Of Gambling Disorder With Schizophreniamentioning
confidence: 99%
“…For instance, the case study reported by Shonin et al (2014e) also used cognitive-behavior therapy along with diary keeping, behavioral experiments, goal setting, and psycho-education. The authors also reported that the intervention employed a broad range of meditation exercises and meditation-based dialogue techniques that may exert specific training (and, therefore, time) demands on the part of the therapist.…”
Section: Mindfulness In the Treatment Of Gambling Disordermentioning
confidence: 99%
“…Future research and dialogue should also focus on addressing some of the issues that currently hinder the wide-scale operationalization of mindfulness as an addiction treatment. Such issues include the need for a more established training and assessment curriculum for MBI instructors who, in some instances, may have as little as one year's mindfulness practice and teaching experience following completion of a single 8-week training course (Shonin et al 2014e;Van Gordon et al 2015). Additionally, diverse models of mindfulness are employed in different MBIs, and this is problematic when attempting to identify the precise attributes of mindfulness practice that are mechanistically active in the treatment of gambling disorder.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…10,11 The cultivation of mindfulness can create a significant change in the way individuals approach their experiences, allowing the development of greater stability, meaning, flexibility, and less reactivity. Examples of mindfulness-based interventions used in addictions include Mindfulness-Based Relapse Prevention, 12 Mindfulness-Based Stress Reduction, 13 Meditation Awareness Training, 14 MindfulnessBased Cognitive Therapy, 15 and Mindfulness-Enhanced Cognitive Behavior Therapy.…”
Section: Introductionmentioning
confidence: 99%